2012
DOI: 10.1038/oby.2012.138
|View full text |Cite
|
Sign up to set email alerts
|

Increased Death of Adipose Cells, a Path to Release Cell‐Free DNA Into Systemic Circulation of Obese Women

Abstract: Remodeling of adipose tissue is required to support the expansion of adipose mass. In obesity, an increased death of adipocytes contributes to the accelerated cellular turnover. We have shown that obesity in pregnancy is associated with metabolic and immune alterations in the adipose tissue. In this study we characterized the mechanisms responsible for increased death of adipose cells of pregnant obese women and its functional consequences. We postulated that a higher turnover of dead cells in white adipose ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 41 publications
5
108
1
1
Order By: Relevance
“…The decrease in fetal cfDNA with maternal weight is compatible with the plasma concentration of other fetoplacental products and can be attributed to a dilutional effect [22]. In contrast, maternal cfDNA levels increase with weight and recent evidence suggests that with increased weight there is active remodeling of adipose tissue with accelerated turnover of adipocytes [34]. …”
Section: Discussionmentioning
confidence: 91%
“…The decrease in fetal cfDNA with maternal weight is compatible with the plasma concentration of other fetoplacental products and can be attributed to a dilutional effect [22]. In contrast, maternal cfDNA levels increase with weight and recent evidence suggests that with increased weight there is active remodeling of adipose tissue with accelerated turnover of adipocytes [34]. …”
Section: Discussionmentioning
confidence: 91%
“…This is also true for other fetoplacental products, including free β-hCG and PAPP-A. A contributing factor to the decrease in fetal fraction with increasing maternal weight is the increase in maternal cfDNA levels because with increased weight there is active remodeling of adipose tissue with accelerated turnover of adipocytes [22,23]. In terms of the association of fetal fraction with serum-free β-hCG and PAPP-A, these metabolites are produced by the placenta and inevitably their maternal serum concentration provides an indirect measure of placental mass.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal obesity is associated with an increased amount of total cell-free DNA, resulting from adipocyte necrosis. 22 Fetal fraction is the percentage of cell-free fetal DNA as compared with total cell-free DNA; thus, an increase in total cell-free DNA would result in a decreased fetal fraction. 23 Prior studies have demonstrated that the fetal fraction is positively correlated with gestational age and negatively correlated with maternal weight.…”
Section: Discussionmentioning
confidence: 99%